2007
DOI: 10.1111/j.1365-2567.2007.02573.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo kinetics of human natural killer cells: the effects of ageing and acute and chronic viral infection

Abstract: Summary Human natural killer (NK) cells form a circulating population in a state of dynamic homeostasis. We investigated NK cell homeostasis by labelling dividing cells in vivo using deuterium‐enriched glucose in young and elderly healthy subjects and patients with viral infection. Following a 24‐hr intravenous infusion of 6,6‐D2‐glucose, CD3– CD16+ NK cells sorted from peripheral blood mononuclear cells (PBMC) by fluorescence‐activated cell sorter (FACS) were analysed for DNA deuterium content by gas chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
191
2
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(204 citation statements)
references
References 31 publications
8
191
2
3
Order By: Relevance
“…However, it could be argued that the NK cells observed after HSCT might be cells that were already mature and educated in the graft, survived in vivo after transplantation, rather than progenitor-derived NK cells educated in the recipient. However, this hypothesis seems unlikely considering the half-life of mature NK cells, which does not usually exceed 10 days in mice and humans 31,32 and 70 days for the so-called "long-lived" memory-like NK cells recently described in mice. 33,34 Because most samples in the present study were collected 3 months or later after HSCT (Table 1), the NK-cell populations we assessed most probably originated from engrafted progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…However, it could be argued that the NK cells observed after HSCT might be cells that were already mature and educated in the graft, survived in vivo after transplantation, rather than progenitor-derived NK cells educated in the recipient. However, this hypothesis seems unlikely considering the half-life of mature NK cells, which does not usually exceed 10 days in mice and humans 31,32 and 70 days for the so-called "long-lived" memory-like NK cells recently described in mice. 33,34 Because most samples in the present study were collected 3 months or later after HSCT (Table 1), the NK-cell populations we assessed most probably originated from engrafted progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…2 After transplantation, the distinct cell lineages of the developing immune system reconstitute at highly different rates; T-cell recovery is very low, but new NK cells are prevalent and integrate this system within 2-3 weeks, suggesting that NK cells could play a remarkable role following hematopoietic transplantation. 3,4 Treatment of leukemia with transplantation of allogenic bone marrow or stem cells from peripheral blood stem cells is limited by the scarcity of human leukocyte antigen (HLA)-matched related or unrelated donor; only 50-60% of patients are eligible. Pioneering results of Ruggeri et al 5 have reported that allogeneic NK cells can mediate antileukemic effects against acute myeloid leukemia (AML) after haploidentical hematopoietic stem-cell transplantation (HSCT), with KIR ligand/KIR ligand incompatibility in the graft-versus-host (GvH) direction.…”
Section: Introductionmentioning
confidence: 99%
“…Aging also impacts on the kinetics of NK cells [97]. NK cells from elderly have a significantly decreased proliferation and production rate which means with the maintained NK cell number that there is an increased proportion of longliving NK cells which can be related to the increased proportion of CD56 dim NK cells.…”
Section: Nk Cell Phenotype and Subpopulation Changes With Agingmentioning
confidence: 99%